Return of beverage and food companies in Indonesia and its factors - Dirvi Surya Abbas; Imam Hidayat (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: This study aimed to determine the impact on stock returns of food and beverage companies in Indonesia during the period 2013-2018 of instrument finance and systemic risk. Methodology: The sampling technique used purposive sampling. Based on the predetermined criteria, eight companies. Data used secondary data obtained from IDX. The method used is regression analysis logistic panel data. Results: Return on equity & systematic risk affected stock returns. Price earning ratio & debt to equity ratio did not affect stock returns. Limitation: The data used is only for food and beverage companies and does not include manufacturing companies as a whole. Contribution: Investors are expected to analyze the company's condition that will invest their capital; besides using technical analysis, it is also better to use fundamental analysis. Keywords: Instrument finance, Systematic risk, Return